2018
DOI: 10.1002/adma.201706702
|View full text |Cite
|
Sign up to set email alerts
|

Excitons and Trions in One‐Photon‐ and Two‐Photon‐Excited MoS2: A Study in Dispersions

Abstract: Herein, various dispersions of MoS obtained by means of liquid phase exfoliation are spectroscopically, (spectro-) electrochemically, and microscopically characterized. At the core of these studies are transient absorption assays. Importantly, small-angle X-ray scattering measurements are employed to corroborate the exfoliated character of the MoS flakes in dispersion, on the one hand, and to correlate the results with TEM, AFM, and Raman characterization in the solid state, on the other. It is, then, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 47 publications
8
49
0
2
Order By: Relevance
“…It is found that both values of τ 1 and τ 2 are independent of the wavelengths. The ultrafast relaxation times (<100 ps) of GDY have been found, which indicate the outstanding potential of GDY in photonics and optoelectronics among the mainstream 2D materials such as BP, [ 29 ] MoS 2 , [ 30 ] and GeSe. [ 25b ] This ultrafast relaxation times can be attributed to the phonon–phonon scattering and the fast relaxation processes of the photogenerated carrier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that both values of τ 1 and τ 2 are independent of the wavelengths. The ultrafast relaxation times (<100 ps) of GDY have been found, which indicate the outstanding potential of GDY in photonics and optoelectronics among the mainstream 2D materials such as BP, [ 29 ] MoS 2 , [ 30 ] and GeSe. [ 25b ] This ultrafast relaxation times can be attributed to the phonon–phonon scattering and the fast relaxation processes of the photogenerated carrier.…”
Section: Methodsmentioning
confidence: 99%
“…[ 25b ] This ultrafast relaxation times can be attributed to the phonon–phonon scattering and the fast relaxation processes of the photogenerated carrier. [ 30 ] The ultrabroad ESA characteristics and ultrafast relaxation times of GDY demonstrate the great potential of GDY for applications in photonics and photoelectronics devices, such as PDs, high‐speed modulators, all‐optical switcher, and saturable absorbers.…”
Section: Methodsmentioning
confidence: 99%
“…These dynamics resemble those already reported for exfoliated MoS 2 . [21] For 2, excited states of both components are observed to participate in the decay cascade ( Figure 5). Selective excitation into the Soret-band absorption of 2 affords a photoinduced absorption at l = 450 nm and ground-state bleaching of the bands at l = 617 and 679 nm.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Based on UV/Vis assays, 1 possesses characteristic absorption features, the Soret band at 348 nm and Q bands at 613, 653, and 680 nm . In exfoliated MoS 2 , there are A and B excitonic transitions at 668 and 605 nm, respectively, followed by direct transitions from the valence to the conduction band at 456 and 374 nm (Supporting Information, Figure S5) . Focusing on 2 , the major absorption due to ZnPc at around 680 nm masks the excitonic A band of MoS 2 , while, in reverse, the excitonic B band of MoS 2 overshadows the ZnPc absorption centered at 613 nm (Figure a).…”
Section: Figurementioning
confidence: 99%